ETV4 Mutation in a Patient with Congenital Anomalies of the Kidney and Urinary Tract - Chen, Jing; van der Ven, Amelie T.; Newman, Joseph A.; Vivante, Asaf; Mann, Nina; Aitkenhead, Hazel; Shril, Shirlee; Ityel, Hadas; Schulz, Julian; Schmidt, Johanna Magdalena; Widmeier, Eugen; Gileadi, Opher; et al. (International Journal of Pediatrics and Child Health, 2016)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common reason for chronic kidney disease in children. Although more than 30 monogenic causes have been implicated in isolated forms of human CAKUT so far, the vast majority remains elusive. To identify novel monogenic causes of CAKUT we applied homozygosity mapping, together with whole exome sequencing, in a patient from consanguineous descent with isolated CAKUT. We identified a homozygous missense mutation (p.Arg415His) of the Ets Translocation Variant Gene 4 (ETV4). The transcription factor ETV4 is a downstream target of the GDNF/RET signaling pathway that plays a crucial role in kidney development. We show by means of electrophoretic mobility shift assay that the Arg415His mutant causes loss of the DNA binding affinity of ETV4 and fails to activate transcription in a cell-based luciferase reporter assay. We furthermore investigated the impact of the mutant protein on cell migration rate. Unlike wildtype ETV4, the Arg415His mutant failed to rescue cell migration defects observed in two ETV4 knock-down cell-lines. We therefore identified and functionally characterized a recessive mutation in ETV4 in a human patient with CAKUT. We hypothesize that the pathomechanism of this mutation could be via loss of the transcriptional function of ETV4, and a resulting abrogation of GDNF/RET/ETV4 signaling pathway.